2006
DOI: 10.1016/j.atmosenv.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sugars as source indicators of biogenic organic carbon in aerosols collected above the Howland Experimental Forest, Maine

Abstract: Bulk aerosols (> 1 μm) were collected continuously above the canopy at the Howland Experimental Forest, Maine, USA from May to October 2002. Each sample integrated over an approximately two-week period. Mono-and disaccharide sugars were extracted using a microscale technique and were analyzed as their TMS derivatives by GC-MS. Concentrations of total aerosol sugars ranged from 10 to 180 ng m -3 . Glucose was the most abundant sugar (40-75% of the total sugars). The monosaccharides arabinose, fructose, galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
179
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(211 citation statements)
references
References 43 publications
15
179
4
1
Order By: Relevance
“…For example, Bauer et al (2008) reported that arabitol and mannitol are tracers for the quantification of airborne fungal spores. Trehalose is present in a variety of microorganisms (fungi, bacteria and yeast), a few higher plants and invertebrates (Medeiros et al, 2006). In the present study, the concentrations of these three tracers at Yufa were higher than at PKU (Fig.…”
Section: Plant Emission and Microbial Inputmentioning
confidence: 48%
“…For example, Bauer et al (2008) reported that arabitol and mannitol are tracers for the quantification of airborne fungal spores. Trehalose is present in a variety of microorganisms (fungi, bacteria and yeast), a few higher plants and invertebrates (Medeiros et al, 2006). In the present study, the concentrations of these three tracers at Yufa were higher than at PKU (Fig.…”
Section: Plant Emission and Microbial Inputmentioning
confidence: 48%
“…Primary saccharides are an important class of organic compounds in atmospheric aerosols (Medeiros et al, 2006;Wan and Yu, 2007;Yttri et al, 2007;Fu et al, 2008). They are completely water-soluble and thus contribute to WSOC in aerosol.…”
Section: Diurnal Variations Of Primary Saccharidesmentioning
confidence: 99%
“…For example, mannitol, together with arabitol, has been reported as tracers for the airborne fungal spores (Bauer et al, 2008). Trehalose is present in a large variety of microorganisms (fungi, bacteria and yeast), and a few higher plants and invertebrates (Medeiros et al, 2006).…”
Section: Diurnal Variations Of Primary Saccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioaerosol (bacteria, fungi, viruses, pollen, cell debris) contains primary saccharides such as glucose and sucrose (Medeiros et al, 2006). Arabitol and mannitol can be used as tracers for airborne fungal spores (Bauer et al, 2008), and are also the main carbohydrates in lichens and bacteria (Medeiros et al, 2006).…”
Section: Introductionmentioning
confidence: 99%